2011
DOI: 10.3945/jn.110.128249
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in Infancy Is Not Associated with Inflammatory Status in Healthy Adolescents

Abstract: It has been suggested that breast-feeding (BF) may be associated with a decreased risk of cardiovascular disease in adulthood. A low-grade inflammation is associated with an increased risk of cardiovascular disease, even in apparently healthy children. The objective of this study was to assess the potential modulating effect of BF on the inflammatory status of healthy adolescents. Information on BF (duration) was obtained from parental records in 484 of 1040 healthy European urban adolescents (56.4% females) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
3
2
Order By: Relevance
“…Innate immune responses differ between breast-fed and formula-fed infants during the first month of life (39). Later differences in systemic inflammatory parameters have only been shown in selected groups; breast feeding was associated with higher CRP in adolescents in a follow-up study on preterm infants (9) but not in another study on term infants (40). In this study, we observed no differences in hsCRP between the EF and SF groups.…”
Section: Discussioncontrasting
confidence: 58%
“…Innate immune responses differ between breast-fed and formula-fed infants during the first month of life (39). Later differences in systemic inflammatory parameters have only been shown in selected groups; breast feeding was associated with higher CRP in adolescents in a follow-up study on preterm infants (9) but not in another study on term infants (40). In this study, we observed no differences in hsCRP between the EF and SF groups.…”
Section: Discussioncontrasting
confidence: 58%
“…However, the influence of breastfeeding duration on obesity-related inflammation is still controversial (Labayen et al, 2012;Singhal et al, 2004;Vérier et al, 2011). In this regard, our results show no significant association between BMI in adolescents and breastfeeding duration in their infancy.…”
Section: Discussioncontrasting
confidence: 65%
“…Socioeconomic status and educational level of the parents are also related to inflammation in adolescents (Chiang et al, 2015). The inclusion of these variables as confounders in their analysis might be why Vérier et al (2011) did not find an association between breastfeeding and inflammation. We did not include socioeconomic status (the data were unavailable) in our analyses in the present study, but we did include maternal educational level.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Breastfeeding exclusivity was also inversely associated with gut inflammation in infants [111]. Moreover, the anti-inflammatory effect of breastfeeding may persist into adolescence [112] and adulthood [113,114], independent of other risk factors; however, not every study found this association [115,116].…”
Section: Findings and Discussionmentioning
confidence: 99%